Redox reactivity of the heme Fe3+/Fe2+ couple in native myoglobins and mutants with peroxidase-like activity - BATTISTUZZI, Gianantonio; BELLEI, Marzia; BORTOLOTTI, Carlo Augusto; SOLA, Marco; L. CASELLA; E. MONZANI; R. RONCONE (JBIC Journal of Biological Inorganic Chemistry, 2007)
The reaction enthalpy and entropy for the one-electron reduction of the ferric heme in horse heart and sperm whale aquometmyoglobins (Mb) have been determined exploiting a spectroelectrochemical approach. Also investigated were the T67R, T67K, T67R/S92D and T67R/S92D Mb-H variants (the latter containing a protoheme-l -histidine methyl ester) of sperm whale Mb, which feature peroxidase-like activity. The reduction potential (E°′) in all species consists of an enthalpic term which disfavors Fe3+ reduction and a larger entropic contribution which instead selectively stabilizes the reduced form. This behavior differs from that of the heme redox enzymes and electron transport proteins investigated so far. The reduction thermodynamics in the series of sperm whale Mb variants show an almost perfect enthalpy-entropy compensation, indicating that the mutation-induced changes in <EquationSource Format="TEX"> </EquationSource> are dominated by reduction-induced solvent reorganization effects. The modest changes in E°′ originate from the enthalpic effects of the electrostatic interactions of the heme with the engineered charged residues. The small influence that the mutations exert on the reduction potential of myoglobin suggests that the increased peroxidase activity of the variants is not related to changes in the redox reactivity of the heme iron, but are likely related to a more favored substrate orientation within the distal heme cavity.